2011
DOI: 10.1038/modpathol.2011.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and molecular characterization of colorectal micropapillary carcinoma

Abstract: Invasive micropapillary carcinoma is associated with frequent lymph node metastasis and adverse clinical outcome. Initially described as a variant of breast and ovarian carcinoma, it has subsequently been found in other organs, most recently the colon. Reports of colorectal micropapillary carcinoma to date are limited in number, and their molecular profile has not been established. The aims of the present study were to analyze their clinicopathological features and molecular profile, and compare them with thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
92
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 27 publications
5
92
2
4
Order By: Relevance
“…7 Several studies showed the prevalence of micropapillary carcinoma was 9-19% in colorectal carcinoma, and it was associated with aggressive histological features, including higher levels of lymphovascular invasion and perineural invasion, more frequent lymph node and distant metastases, and higher TNM stages (III/ IV). [8][9][10][11] In concordance with previous studies, we identified 10% of colorectal carcinoma with micropapillary carcinoma component from our cohort (55/561 cases), and micropapillary carcinoma was significantly associated with higher Figure 2 Kaplan-Meier survival analysis (log rank test). (a and b) Non-micropapillary carcinoma patients experience significantly better overall survival rates (Po0.0001, a) and disease-free survival rates (Po0.0001, b) than patients with micropapillary carcinoma.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…7 Several studies showed the prevalence of micropapillary carcinoma was 9-19% in colorectal carcinoma, and it was associated with aggressive histological features, including higher levels of lymphovascular invasion and perineural invasion, more frequent lymph node and distant metastases, and higher TNM stages (III/ IV). [8][9][10][11] In concordance with previous studies, we identified 10% of colorectal carcinoma with micropapillary carcinoma component from our cohort (55/561 cases), and micropapillary carcinoma was significantly associated with higher Figure 2 Kaplan-Meier survival analysis (log rank test). (a and b) Non-micropapillary carcinoma patients experience significantly better overall survival rates (Po0.0001, a) and disease-free survival rates (Po0.0001, b) than patients with micropapillary carcinoma.…”
Section: Discussionsupporting
confidence: 90%
“…Previous published studies found that the proportion of micropapillary carcinoma to the entire tumor ranged from 5 to 80%, and defined micropapillary carcinoma as carcinoma with at least 5% of micropapillary components. [8][9][10][11] On the other hand, as the identification of tumorinitiating cells, also referred to as cancer stem cells, in acute myeloid leukemia, their presence has also been identified in a number of solid tumor types, such as breast, lung, ovarian, brain, and colon cancer. [12][13][14][15][16][17] Emerging evidence suggests that stem cells have a crucial role not only in the embryonic development and maintenance of mature normal tissues, but also in the development of malignancies and disease progression associated with poor prognosis.…”
mentioning
confidence: 99%
“…To date, the majority of reported cases are single case report [8,9,10,11,12,13,14,15]. However, there are only a few reports on a large scale clinicopathological study of colon cancer with MPP [16,17,18,19,20]. Although colon cancer with MPP behaves aggressively even in TNM Stage I and II, there is little evidence on the clinical outcome in this tumour [16].…”
Section: Introductionmentioning
confidence: 99%
“…Except for the ovary, micropapillary carcinoma arising in many organs seems to pursue an aggressive clinical course because of frequent invasion into lymphatic spaces, metastasis into lymph nodes, or systemic metastasis (Verdú et al;Amin et al, 2002;Amin et al, 1994;Nassar;Nassar et al;Paterakos et al;Siriaunkgul & Tavassoli;Zekioglu et al;Haupt et al;Kim et al;Kuroda et al;Sakamoto et al;Wen et al;Xu et al). Micropapillary carcinoma of the colon macroscopically seems to be indistinguishable from conventional adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The micropapillary carcinoma is regarded as an aggressive variant of adenocarcinoma in any location described, namely bladder, lung, pancreas, salivary glands and recently colon, rectum and stomach (Verdú et al, 2011;Amin et al, 2002;Amin et al, 1994;Nassar, 2004;Nassar et al, 2001;Paterakos et al, 1999;Siriaunkgul & Tavassoli, 1993;Zekioglu et al, 2004). Histologically is characterized by papillary cell clusters surrounded by clear spaces.…”
Section: Introductionmentioning
confidence: 99%